2023
DOI: 10.1155/2023/1094267
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Clinically Relevant Executive Functions Tests Performance after COVID-19

Abstract: It is widely known that COVID-19 has a number of prolonged effects on general health, wellbeing, and cognitive functioning. However, studies using differentiated performance measures of cognitive functions are still not widely spread making it hard to assess the exact functions that get impaired. Taking into account the similarities between post-COVID ‘brain fog’ and chemofog, we hypothesized that executive functions (EF) would be impaired. Literature search yielded six studies with 14 effect sizes of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…We did not find an association between the severity of the disease and a worse neurocognitive performance. Other studies have also indicated no link between the disease’s severity and neuropsychological performance [ 10 , 37 , 38 , 39 , 40 , 41 , 42 ]. No neuropsychological differences were observed between the four groups considering severity, indicating that an association between disease severity and neurocognitive performance cannot be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find an association between the severity of the disease and a worse neurocognitive performance. Other studies have also indicated no link between the disease’s severity and neuropsychological performance [ 10 , 37 , 38 , 39 , 40 , 41 , 42 ]. No neuropsychological differences were observed between the four groups considering severity, indicating that an association between disease severity and neurocognitive performance cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…In long COVID-19 studies, the neurocognitive deficit termed ‘brain fog’ was the most common, affecting at least one-third of patients [ 33 , 34 ] from moderate (58.7%) to severe impairment (18.4%) [ 35 ], surpassing the prevalence rates seen in other viral infections [ 29 ]. The most prevalent neuropsychological deficits included attention, memory, dysnomia, executive function, and speed processing [ 4 , 34 , 36 , 37 , 38 , 39 , 40 , 41 ]. While impacting about 86% of patients’ ability to work [ 34 ], these deficits are independent of initial disease severity [ 36 , 37 , 42 ] and are more related to mental health status [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results appear to suggest some form of cognitive deficits associated with COVID-19 in the acute and shortterm follow-up phase, revealing that people with COVID-19 had poorer general cognitive functioning (measured with RUDAS-P) compared to people without COVID-19 between assessment in the acute phase and 6 months after infection (Crivelli et al, 2022). In this sense, objective measures show that executive functions (such as inhibition, updating, and set-shifting) also get impaired, and effects range from small to large, and generally, decreases in performance are related to advanced age and illness severity (Velichkovsky et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This cognitive dysfunction (sometimes referred to as brain fog) occurring in long COVID patients has been attracting more attention 6 . By now we know that COVID is associated with cognitive dysfunction with most impact on attention, memory and executive functioning 7,8 .…”
Section: Introductionmentioning
confidence: 99%